Gastronomy tourism and the COVID-19 pandemic crisis - Anna Ostrowska-Tryzno; Anna Pawlikowska-Piechotka (Jan Długosz University in Częstochowa, 2022)
This paper aims to consider a sector of cultural tourism: gastronomy tourism (also known as food tourism, culinary tourism) in the context of the COVID-19 pandemic crisis. This is a conceptual paper, based mainly on the critical review of academic literature and UN WTO, UN WHO and UNESCO documents. By synthesising available data and research results, this paper provides an assessment of the present situation of gastronomy tourism, and tries to formulate some trends possible to be developed in the future, once the pandemic is over (as a potential role of culinary tourism in the revival of the whole sector). The research questions focused on the meaning and tradition of gastronomy tourism, conse- quences of the COVID-19 crisis and post-pandemic regeneration of the sector. The paper concludes that trends seen in gastronomy tourism sector before lockdown are no longer applicable during the COVID-19 pandemic crisis. The new technologies helped to overcome some of the challenges which this industry currently faces. Several potential trends might be developed after the pandemic crisis, serving as local food and local culinary tradition promotion. Suggestions are provided for further research as discussion about more resilient, sustainable and inclusive gastronomy tourism in the future as well as recovery practices within the domestic hospitality are important.